Pengaruh Model Pembelajaran Kooperatif Tipe Make a Match Terhadap Motivasi Belajar Siswa Pada Materi Sistem Tata Surya di Sekolah Dasar - Rachman, Emah Fauziyah; Setiyawati, Enik (LP. Ma'arif Janggan Magetan, 2023)
This research was conducted to analyze the effect of the make a match cooperative learning model on students' learning motivation. Motivation to learn is important in the learning process because with motivation to learn, individuals can have goals and enthusiasm for learning. The make a match type cooperative learning model is a learning model that invites students to look for answers to a question or pair of a concept through a pair card game. The research method used is a one group pretest-posttest design. The experimental group will be given a treatment, namely the application of the make a match model to the material of the solar system. Whereas the control class was not given treatment, but it was given another method, namely the lecture and question and answer method. After that, a post test is given, using a questionnaire sheet at the final stage in order to find out how much influence the make a match learning model has on students' learning motivation in the solar system material. Based on the analysis carried out, it can be concluded that there is an influence of the make a match type cooperative learning model on student learning motivation. This can be seen from the increased learning motivation of students in the high N-Gain category after being given learning with this model.